Factors Affecting the Internal Audit Effectiveness in the Viewpoint of Audit Committee Members - Aboozar Okhravi Joghan; Nezamoddin Rahimian; Maryam GharehDaghi (بررسی‌های حسابداری و حسابرسی, 2018)
Objective: Thisresearch has studied the effect of five main factors including competence of internal audit department, size of internal audit department, relationship between internal and external audit, management support for internal audit, and independence of internal audit on the internal audit effectiveness in companies that listed in the Tehran Stock Exchange in 2017. Methods: Data was collected using paper and electronic questionnaires which their validity and reliability were confirmed. The population of this study included members of the audit committee in companies that listed in the Tehran Stock Exchange in 2017. Finally, 300 valid questionnaires were analyzed. In this study both descriptive and inferential analyses were used. Inferential statistics was used to confirm the validity of the model and confirmatory, and factor analysis and structural equation modeling were used to test the hypotheses. Results: Findings from the research showed that competence of internal audit department, size of internal audit department, relationship between internal and external audit, management support for internal audit, and independence of internal audit have a positive and direct effect on internal audit effectiveness. Conclusion: Promotion of five main factors including competence of internal audit department, size of internal audit department, relationship between internal and external audit, management support for internal audit, and independence of internal audit in companies that listed in the Tehran Stock Exchange led to an increase in the effectiveness of internal auditing and lack of attention each of these factors has reduced the effectiveness of internal auditing in these companies.